eIF5A and EF-P: two unique translation factors are now traveling the same road - Rossi, Danuza [UNESP]; Kuroshu, Reginaldo; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP] (Wiley-Blackwell, 2014)
Translational control is extremely important in all organisms, and some of its aspects are highly conserved among all primary kingdoms, such as those related to the translation elongation step. The previously classified translation initiation factor 5A (eIF5A) and its bacterial homologue elongation factor P (EF-P) were discovered in the late 70's and have recently been the object of many studies. eIF5A and EF-P are the only cellular proteins that undergo hypusination and lysinylation, respectively, both of which are unique posttranslational modifications. Herein, we review all the important discoveries related to the biochemical and functional characterization of these factors, highlighting the implication of eIF5A in translation elongation instead of initiation. The findings that eIF5A and EF-P are important for specific cellular processes and play a role in the relief of ribosome stalling caused by specific amino acid sequences, such as those containing prolines reinforce the hypothesis that these factors are involved in specialized translation. Although there are some divergences between these unique factors, recent studies have clarified that they act similarly during protein synthesis. Further studies may reveal their precise mechanism of ribosome activity modulation as well as the mRNA targets that require eIF5A and EF-P for their proper translation. (C) 2014 John Wiley & Sons, Ltd.